(untitled) (Journal of the College of Basic Education, 2023)
In her research tagged (The Monod Arma in the Iraqi Theatre), the researcher reviews a theatrical phenomenon It grew contiguous with the spread of theatrical art in Iraq and coincided with its establishment, to become widespread It has increased significantly since the sixties of the last century, for various reasons, the most important of which may be the low production cost. In addition to the social, political and intellectual reasons. The researcher found that the first play Monod Armia holds the status of leadership in